2009
DOI: 10.1007/s11262-009-0368-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a new bat gammaherpesvirus in the Philippines

Abstract: A new bat herpesvirus was detected in the spleen of an insectivorous bat (Hipposideros diadema, family Hipposideridae) collected on Panay Island, the Philippines. PCR analyses were performed using COnsensus-DEgenerate Hybrid Oligonucleotide Primers (CODEHOPs) targeting the herpesvirus DNA polymerase (DPOL) gene. Although we obtained PCR products with CODEHOPs, direct sequencing using the primers was not possible because of high degree of degeneracy. Direct sequencing technology developed in our rapid determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 9 publications
(10 reference statements)
2
21
0
2
Order By: Relevance
“…dupreanum , Pteropus lylei (a nectarivorous bat), Lonchophylla thomasi , and an unidentified bat [5, 6]. Several betaherpesviruses and gammaherpesviruses have also been detected in bats from the families Vespertilionidae [7,8], Miniopteridae [9, 10], Pteropodidae [11], Hipposideridae [12] and Rhinolophidae [8]. Nevertheless, with the exception of a few vespertilionid gammaherpesviruses described by Wibbelt et al [7], relatively little is known about the phylogenetic relationships among the different bat herpesvirus species.…”
Section: Introductionmentioning
confidence: 99%
“…dupreanum , Pteropus lylei (a nectarivorous bat), Lonchophylla thomasi , and an unidentified bat [5, 6]. Several betaherpesviruses and gammaherpesviruses have also been detected in bats from the families Vespertilionidae [7,8], Miniopteridae [9, 10], Pteropodidae [11], Hipposideridae [12] and Rhinolophidae [8]. Nevertheless, with the exception of a few vespertilionid gammaherpesviruses described by Wibbelt et al [7], relatively little is known about the phylogenetic relationships among the different bat herpesvirus species.…”
Section: Introductionmentioning
confidence: 99%
“…that have been recently discovered in bats include astroviruses, adeno-associated viruses (AAVs), adenoviruses, herpesviruses, and polyomavirus (8,9,13,31,32,35,37,39,40,42,61,62,68). For example, it was recently reported that a newly identified adenovirus isolated from bat guano was capable of infecting various vertebrate cell lines, including those of humans, monkeys, dogs, and pigs (35).…”
mentioning
confidence: 99%
“…Alpha-, beta-and gammaherpesviruses have all been discovered in bats. Using PCR, Wibbelt et al (94), Molnar et al (56), and Watanabe et al (93) discovered gamma-and betaherpesviruses in bats. Fifteen alphaherpesviruses were isolated from bats in Cambodia and Madagascar (65), and a betaherpesvirus (bat betaher-aligned.…”
mentioning
confidence: 99%